The Importance of REST for Development and Function of Beta Cells - Martin, David; Grapin-Botton, Anne (Frontiers in Cell and Developmental Biology, 2017)
Beta cells are defined by the genes they express, many of which are specific to this cell type, and ensure a specific set of functions. Beta cells are also defined by a set of genes they should not express (in order to function properly), and these genes have been called forbidden genes. Among these, the transcriptional repressor RE-1 Silencing Transcription factor (REST) is expressed in most cells of the body, excluding most populations of neurons, as well as pancreatic beta and alpha cells. In the cell types where it is expressed, REST represses the expression of hundreds of genes that are crucial for both neuronal and pancreatic endocrine function, through the recruitment of multiple transcriptional and epigenetic co-regulators. REST targets include genes encoding transcription factors, proteins involved in exocytosis, synaptic transmission or ion channeling, and non-coding RNAs. REST is expressed in the progenitors of both neurons and beta cells during development, but it is down-regulated as the cells differentiate. Although REST mutations and deregulation have yet to be connected to diabetes in humans, REST activation during both development and in adult beta cells leads to diabetes in mice.